Selectivity of essential oils to the egg parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) - Ewerton Santos Sombra, Kassio (Revista Ciência Agronômica, 2021)
The diversity of arthropod pests has required the combined use of various control methods. The application of essential oils showing insecticidal, repellent or phage-inhibiting activity, together with the release of natural enemies, can improve integrated pest management provided the oils display selectivity. The aim of this study was to evaluate the selectivity of the oils of rosemary pepper [Lippia origanoides Kunth (Verbenaceae)], citronella [Cymbopogon winterianus Jowitt. (Poaceae)] and lemongrass [C. citratus (DC) Stapf.] for Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae), comparing fi ve concentrations (0.01, 0.05, 0.1, 0.5 and 1.0%), and a control (neutral detergent at 1.0%). Residual toxicity was evaluated using adult mortality, calculating lethal concentrations (LC50) in addition to the reductions in parasitism in eggs of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) and selectivity for the par asitoids. The three oils showed selectivity for the parasitoid T. pretiosum, resulting in a mortality rate of between 17.2% (rosemary pepper) and 32.2% (lemongrass) at the lowest concentration. The essential oil of rosemary pepper stood out with an LC50 of 0.43%, a reduction of only 22% in parasitism (Class 1 - Innocuous) and 88.0% emergence, at a dose of 0.01%. The LC50 of the lemongrass oil was 0.15%, with a 34.0% reduction in parasitism (Class 2 - Slightly harmful) and 74.0% emerged adults. For the citronella oil, the LC50 was 0.12%, with a reduction of 46.0% (Class 2 - Slightly harmful) and emergence of 62.0%. The selectivity of the essential oils makes possible to release T. pretiosum, integrating biological control with botanical insecticides, as long as non-sprayed eggs are parasitised by T. pretiosum.